Using Strategic Communications to Engage Stakeholders in Tax Reform - Rahman, Shaela (World Bank, Washington, DC, 2012)
Strategic communications is used to build support and local ownership for reform initiatives while diffusing stakeholder opposition. It addresses the critical 'people' side of the reform process by fostering dialogue between stakeholders, changing perceptions, and strengthening the capacity of government to assist taxpayers. This note outlines an approach tested in tax reform projects in the Republic of Yemen and Sierra Leone, where strategic communications has been used to identify, and then systematically inform and engage relevant stakeholders a process that has proved essential to reform implementation and acceptance. This note also highlights the experience of the Lao People's Democratic Republic, where a multimedia informational campaign preceded the introduction of the value-added tax (VAT), influencing public opinion and paving the way for the reform.